The confrontation of James Taylor Junior (Leader of the exclusive Brethren) and his supporters ; vol. 2 - Calvey, Hubert (Lancashire, UK H. Calvey, 1967)
Contents : v. 2 : Being nine further letters (revised) addressed to James Taylor Jr., 1965-6 on "Behaviour in the house of God" and extract of letter of 1965 to Alfred J.Gardiner (with appended note).
Keywords: Brethren movement -- Exclusive Brethren -- controversies